Reclaimed Waste Water in Some Middle Eastern Countries - Chatila, Jean G. (2004)
Countries of the Middle East are increasingly suffering from shortages and mismanagement of water, a commodity that is becoming of considerable value since water demands are fast approaching the limits of availability. Efficient solutions for water-related problems necessitate the adoption of well-planned policies. The solution must be sought in the optimum use of the available water, and reuse of reclaimed waste water must play a vital part. To meet future water requirements, many countries will have no option but to increase the use of treated waste water and study the viability of waste water reuse alternatives including irrigation of agricultural lands and recharge of groundwater. The cost of waste water treatment depends on the process used and the level of treatment required for a particular use. Data on waste water in the Middle East region are scarce and scattered. The article's main aim is to provide a summary and perspective on the subject and clarify the idea that waste water is not free. This paper describes the different aspects of the waste water—quantities, treatment, potential reuse, and pricing of the treated effluent—in some countries of the Middle East. Many of these countries will have no option but to increase the use of treated waste water—an economically acceptable resource—to reduce the exploitation of scarce water sources and resources. Finally, a set of proposed regulations and recommendations has been developed.